Concepções dos professores de matemática da educação básica do município de Macapá: a elaboração de sequências didáticas como subsídios metodológicos no processo de aprendizagem matemática - COELHO, Larissa Mascarenhas (Instituto Federal do Amapá, 2021)
This study was developed with the objective of rescuing the conceptions of Teachers of the subject of Mathematics in the city of Macapá - AP, who teach in education, regarding the relevance of the use/elaboration of Didactic Sequences in Mathematics Education, besides their reflections about the proposed subject. It is believed that the elaboration of works through didactic sequences symbolizes a pedagogical differential that contributes to the achievement of the objectives expressed in the frameworks of learning rights. The methodology was based on a quantitative and qualitative research, with bibliographic characteristics. The data were collected through the application of a questionnaire through the "Google Forms" platform, remotely to a sample of fourteen volunteer teachers. The results were based on the following specific objectives: to demonstrate the time of the teachers' performance in teaching practice; to verify the level of graduation of teachers in the area of performance; to verify their conceptions about the elaboration of Didactic Sequences; to evidence the relevance of Didactic Sequences in the process of mathematical learning. And in order to favor a precise understanding, the analysis of the results was exposed through graphs and demonstrative tables. In addition, this work seeks to contribute and enrich the collection of research conducted in the field of Didactic Sequences in Mathematics Education, in order to demonstrate the teaching conceptions about methodological subsidies in the process of mathematical learning.